Impact of the Relationship among Financial Development, ICT and English Proficiency on Income Inequality: Evidence from Malaysia - Shaharuddin, Norhasimah; Azam, Abdul Hafiz Mohd; Wahab, Mohd Hafiz Abdul; Karim, Norzitah Abdul; Hilmiyah, Nurul; Shakrein, Sharul Shahida; Osman, Adibah Alawiah (UI Scholars Hub, 2024)
Income inequality is a persistent phenomenon and fundamental issue of concern, especially in this new digital era, because unequal access to finance has long been recognized as a critical mechanism for generating persistent income inequality. ICT tools and approaches are being used widely today due to their convenience, omnipresence and economy. This study examines the influence of financial development, ICT, and English proficiency on income inequality in Malaysia during the period of 1979-2019. The empirical results based on the ARDL bounds test indicated that financial develop- ment and English proficiency support the hypothesis that both factors can reduce the income gap in the long run. While ICT has shown different results, its improvement has only reduced the income gap in the short term. Hence the need for strengthening ICT policy is crucial as it can lead to develop- ment. Mastery of English is also considered to foster economic resilience.